Other-regarding preferences and redistributive politics - Thomas Epper; Ernst Fehr; Julien Senn (University of Zurich, Department of Economics, 2020)
Increasing inequality and associated egalitarian sentiments have again put redistribution on the political agenda. Support for redistribution may also be affected by altruistic and egalitarian preferences, but knowledge about the distribution of these preferences in the broader population and how they relate to political support for redistributive policies is still scarce. In this paper, we take advantage of Swiss direct democracy, where people voted several times in national plebiscites on strongly redistributive policies, to study the link between other-regarding preferences and support for redistribution in a broad sample of the Swiss population. Based on a recently developed non-parametric clustering procedure, we identify three disjunct groups of individuals with fundamentally different other-regarding preferences: (i) a large share of inequality averse people, (ii) a somewhat smaller yet still large share of people with an altruistic concern for social welfare and the worse off, and (iii) a considerable minority of primarily selfish individuals. Controlling for a large number of determinants of support for redistribution, we document that inequality aversion and altruistic concerns play an important role for redistributive voting that is particularly pronounced for above-median income earners. However, the role of these motives differs depending on the nature of redistributive proposals. Inequality aversion has large and robust effects in plebiscites that demand income reductions for the rich, while altruistic concerns play no significant role in these plebiscites.
Keywords: D31; D72; H23; H24; 330; social preferences; altruism; inequality aversion; preference heterogeneity; demand for redistribution